2021
DOI: 10.1002/app.51465
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated weathering effects on mechanical, thermal and viscoelastic properties of kenaf/pineapple biocomposite laminates for load bearing structural applications

Abstract: Natural fibers are exceptional renewable resources to develop biocomposite materials for reducing the negative effects on the environment and producing economical and lightweight materials for load bearing semi‐structural applications. The present study is an attempt to develop kenaf/pineapple reinforced bio‐epoxy biocomposite and investigates thermo‐mechanical and viscoelastic properties under accelerated weathering conditions. The compression molding technique is used to develop biocomposite with four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Storage modulus initially showed a slight drop as the temperature increased, and then a rapid drop in the glass transition region. Similar behaviors and results are observed in studies in the literature 55–57 . While the storage modulus of pure epoxy at room temperature is 2.5 GPa, the storage modulus of nanocomposites with content 0.1 and 0.5% f‐GNF is 3.3 and 3.8 GPa, respectively.…”
Section: Simulation Results and Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Storage modulus initially showed a slight drop as the temperature increased, and then a rapid drop in the glass transition region. Similar behaviors and results are observed in studies in the literature 55–57 . While the storage modulus of pure epoxy at room temperature is 2.5 GPa, the storage modulus of nanocomposites with content 0.1 and 0.5% f‐GNF is 3.3 and 3.8 GPa, respectively.…”
Section: Simulation Results and Discussionsupporting
confidence: 88%
“…For this purpose, first, the storage modulus of pure epoxy and 0.1 and 0.5 wt.% f‐GNF‐epoxy nanocomposite are determined experimentally and simulated with simplified C‐VBO. In DMA tests, the storage modulus (E') is a measure of the elastic response of polymer and GP nanocomposites and the material stiffness represented by the energy absorbed per cycle oscillation 55 . The storage modulus of graphene‐epoxy nanocomposites with different graphene contents were determined experimentally at a frequency of 1 Hz.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 Compared with pure EP, the viscoelastic properties of EP/PPSA are enhanced due to the higher strength and stiffness of PPSA, which would result in higher energy dissipation. [44][45][46][47] Tan δ is decided by the adhesion between EP and PPSA, which in turn depends on temperature. It can be found that the peak of tan δ decreases with increased ratio of PPSA, suggesting a reduction of T g induced by PPSA incorporation.…”
Section: Thermomechanical Propertymentioning
confidence: 99%